MINTAQAVIY TURIZMDA INNOVATSION VA INSTITUTSIONAL MEXANIZMLAR SAMARADORLIGINI BAHOLASHNING KOMPLEKS MODELINING AHAMIYATI (Marketing Journal, 2026)
This article proposes a comprehensive model for assessing the effectiveness of innovative and institutional mechanisms in regional tourism development. The model provides a systematic evaluation of the impact of tourism infrastructure, digital technologies, institutional cooperation, and governance factors on regional tourism growth. The research findings contribute to improving tourism management efficiency, increasing investment attractiveness, and ensuring sustainable development.
Keywords: regional tourism, innovative development, institutional mechanisms, comprehensive assessment model, tourism efficiency, digital transformation, tourism infrastructure, sustainable development.